Exceptionally preserved specimen of Panochthus sp. (Deparment of General Guido, Buenos Aires) reveals unknown anatomic features - Aranciaga Rolando, Alexis Mauro (2024)
In 2021, fieldworks in the General Guido department (Buenos Aires Province) resulted in theextraction of a nearly complete and exceptionally preserved skeleton of Panochthus sp. Thespecimen is assigned to the genus Panochthus by the following diagnostic features: nasal areastrongly inclined anteroventrally, palatal and rostral planes forming a 45º angle; external nasalopenings anteroventrally oriented; molariforms 2 to 8 trilobulated. This specimen (MCHP-001)comes from Chelforó river (36° 55’ 47.8’’ S; 58° 08’ 24.9’’ W) where are exposed outcropspertaining to the Guerrero Member of the Luján Formation (Lujanian Stage, Upper Pleistocene).During the preparation of the skull, elements of the hyoid apparatus and cartilages of the pharynxwere found in articulation. The aim of this work is to redescribe and reinterpret some anatomicalfeatures of Panochthus. Both sigmohyals and the “V” bone are exhibit similar morphology to thosepreviously published. However, we observe that the sigmohyals articulate dorsally with themastoid process of the skull by a spoon-shaped dorsal end. In lateral view, the sigmohyals arealmost vertical while in posterior view are notably oblique and medially inclined. Both sigmohyalsarticulate by a bottom-shaped ventral end with the “V” bone. In lateral view, this latter is stronglyinclined dorsally (forming approximately 70° with the tooth row). Furthermore, a complete thyroidcartilage was found in articulation with the choana. This element is anteroposteriorly long beingnotably longer than that the previously reported for Panochthus. Laterally, this cartilage shows asubtriangular anterior half. This latter shows a flat and crescent-shaped articular facet for the “V”bone. Moreover, on its anterodorsal corner, this cartilage shows a small and laterally projectedprocess for the articulation with the cornual process of the “V” bone. An incomplete cricoidcartilage is observed. This element is arched and is dorsally placed with respect to the thyroidcartilage. All these observations in the hyoid apparatus show a different morphology than that thepreviously published. For example, the sigmohyals are oblique and medially inclined in posteriorview (and not vertically). The almost vertical “V” bone is placed more dorsally, reaching the levelof the floor of the choana. Furthermore, the flat articular facet of the thyroid cartilage for the “V”bone shows that this latter was placed below the thyroid cartilage and not anteriorly (as previouslythought). Given its exceptional preservation MCHP-001 allows us to reinterpret the position of thehyoid apparatus of the genus Panochthus.